2019
DOI: 10.1007/7854_2018_74
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Contributions to Attention and Working Memory

Abstract: The processes of attention and working memory are conspicuously interlinked, suggesting that they may involve overlapping neural mechanisms. Working memory (WM) is the ability to maintain information in the absence of sensory input. Attention is the process by which a specific target is selected for further processing, and neural resources directed toward that target. The content of WM can be used to direct attention, and attention can in turn determine which information is encoded into WM. Here we discuss the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 153 publications
(185 reference statements)
6
43
0
3
Order By: Relevance
“…The prefrontal cortex has particularly been associated with working memory (Bahmani et al, 2019). Consequently, the prefrontal cortex is highly susceptible to the effects of aging and early neurodegeneration (West et al, 2002;Ranchet et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The prefrontal cortex has particularly been associated with working memory (Bahmani et al, 2019). Consequently, the prefrontal cortex is highly susceptible to the effects of aging and early neurodegeneration (West et al, 2002;Ranchet et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the disproportionate prevalence of motor signals among neurons receiving input from visual cortex, reciprocal projections of the FEF to visual cortex originate disproportionately from neurons with memory-related activity (Merrikhi et al, 2017). This implicates the FEF as a possible source of the observed memory-dependent modulation in visual cortex (Bahmani et al, 2019(Bahmani et al, , 2018. It also suggests that memory-related signals may interact with the efficacy of visual inputs arriving in prefrontal cortex.…”
Section: Wm Alters Efficacy Of V4 Input To Fefmentioning
confidence: 98%
“…These characteristics make the FEF a likely place to observe an influence of WM on incoming visual signals, particularly given that the FEF transmits a predominantly WM signal to visual cortex (Merrikhi et al, 2017). Although much is understood about the role of FEF neurons in the control of visually guided saccades (Schiller et al, 1979; Schlag-Rey et al, 1992; Tehovnik et al, 2000), and in the control of visual spatial attention (Bahmani et al, 2019; Gregoriou et al, 2009; Moore and Fallah, 2001), very little is known about how visual, motor, and memory signals are combined within the FEF. Models of FEF microcircuitry generally predict that visual cortical inputs synapse predominantly onto purely visual FEF neurons (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The prefrontal cortex has particularly been associated with working memory. (8) Consequently, the prefrontal cortex is highly susceptible to the effects of aging and early neurodegeneration. (9, 10) A recent meta-analysis pooling functional magnetic resonance imaging studies suggested a gradual and linear decline in prefrontal cortex engagement in older individuals.…”
Section: Introductionmentioning
confidence: 99%